Environmental and energy applications of TiO2 photoanodes modified with alkali metals and polymers. Issue 1 (February 2021) - Abdelnasser, Shady; Al Sakkaf, Reem; Palmisano, Giovanni
Abstract: Owing to several appealing properties such as environmental compatibility, ease of synthesis, photostability, high surface area, non toxicity, and chemical stability, titania (TiO2 ) has found widespread use in numerous technological applications. However, TiO2 also suffers from key disadvantages such as low charge mobility and a wide band gap, restricting many potential uses unless it is modified with suitable materials to narrow its bandgap and improve charge separation and transfer. This review focuses on the research done on alkali metals and conducting polymers to boost the activity of modified TiO2 -based materials. The review also discusses the use of TiO2 photocatalyst in applications such as the photocatalytic degradation of organic pollutants, water splitting for hydrogen formation, and, to a lesser extent, photovoltaics and energy storage devices. It was concluded that upon alkali metal modification, TiO2 photocatalysts exhibit positive band pinning associated with less steepness of the band bending towards the surface leading to a more negative potential under irradiation. Moreover, incorporated conductive polymers can act as a visible light sensitizer maintaining higher photocurrent density, more stable photoelectrochemical (PEC) performance and less charge resistance compared to pristine TiO2 . Graphical Abstract: ga1 Highlights: Focus on major applications of modified TiO2 photoanodes. Address alkali metals (Li, Na, K) and conductive polymers as key components. Discuss organic photodegradation, water splitting, photovoltaic and energy storage devices. Report on the reaction kinetic model and the effect of operating conditions.